2009
DOI: 10.1111/j.1365-2141.2009.07816.x
|View full text |Cite
|
Sign up to set email alerts
|

A new genetic lesion in B‐CLL: a NOTCH1 PEST domain mutation

Abstract: pro-B cells from healthy donors (Zwollo et al, 1997; Sekine et al, 2007).In conclusion, our data show an association between PAX5 aberrant splicing and BCP-ALL. We also provide, for the first time, evidence of imbalance between the full-length and PAX5D2 isoforms as a common event in BCP-ALL. Given the well-documented role of this gene in the development of BCP, the cumulative effect of point mutations and post-transcriptional regulation of alternative splicing of PAX5 pre-mRNA may suggest its primary pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 10 publications
3
79
0
1
Order By: Relevance
“…This latter type of mutations are found in CLL, especially as a frameshift mutation affecting the codon for amino-acid P2515. 4,7,61 Comparable NOTCH1 mutations are also found in B-cell lymphomas 62 and both activation and inactivation of the pathway have been identified in hematopoietic and non-hematopoietic diseases. 63 As with T-cell acute lymphoblastic leukemia, mutations inactivating the FBXW7 gene, which codes normal feedback control of Notch signaling (which also control CMYC stability 64 ), are also observed in CLL.…”
Section: Other Novel Mutations In Lymphomasmentioning
confidence: 99%
“…This latter type of mutations are found in CLL, especially as a frameshift mutation affecting the codon for amino-acid P2515. 4,7,61 Comparable NOTCH1 mutations are also found in B-cell lymphomas 62 and both activation and inactivation of the pathway have been identified in hematopoietic and non-hematopoietic diseases. 63 As with T-cell acute lymphoblastic leukemia, mutations inactivating the FBXW7 gene, which codes normal feedback control of Notch signaling (which also control CMYC stability 64 ), are also observed in CLL.…”
Section: Other Novel Mutations In Lymphomasmentioning
confidence: 99%
“…7,8 By this approach, NOTCH1 mutations occurred in only 2 of 63 (3.2%) cMBL, with a prevalence that was significantly lower than that observed in a large CLL dataset (70 of 603, 11.6%) (P=0.050). In both cases, mutations were represented by a two bp frameshift deletion (c.7544_7545delCT) that represents the most recurrent (~80%) type of NOTCH1 mutation detectable in CLL (Figure 1).…”
Section: Analysis Of Notch1 Mutations In Monoclonal B-cell Lymphocytosismentioning
confidence: 99%
“…[4][5][6] Recently, two independent investigations of the CLL coding genome have revealed that activating mutations of the NOTCH1 proto-oncogene occur in approximately 10% CLL at diagnosis and their frequency increases in advanced disease phases, exemplified by the case of Richter syndrome. 7,8 Initial evidence suggests that NOTCH1 alterations might predict an unfavorable clinical outcome in CLL. The prevalence of NOTCH1 mutations in MBL is currently unknown.…”
Section: Analysis Of Notch1 Mutations In Monoclonal B-cell Lymphocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Dans les LAL-T, les mutations de NOTCH1 peuvent soit faciliter la dissociation de la partie intracellulaire ICN de NOTCH1, soit entraî-ner la perte du domaine PEST de déstabi-lisation de ICN. Ce sont des mutations de ce dernier type qui sont présentes dans les LLC, principalement une mutation « saut de phase » touchant le codon correspondant à l'acide aminé P2515 [9][10][11]. Des mutations de NOTCH1 sont également trouvées dans les lymphomes.…”
unclassified